Breaking the Chains of ‘Pasung’: The Potential Roles of Primary Health Centres and Pharmacists in an Indonesian Setting - Sulisetiorini Sulisetiorini; Yosi Irawati Wibowo; Bruce Sunderland; Adji Prayitno Setiadi (Journal of Public Health and Pharmacy)
Introduction: Healthcare for patients in pasung is often neglected. Limited data is available on the roles of Primary Health Centres (PHCs) as the main providers of primary care in Indonesia. This research aims to explore health services provided for patients in pasung at PHCs and to identify the roles of pharmacists.